Profile of Off-task Behavior in Primary School Students - Saripah, Ipah; Widiastuti, Haning Tri (Universitas Pendidikan Indonesia, 2019)
As an effort to achieve the developmental tasks of primary school age children, they are expected to obtain the basics of knowledge that are considered important to successfully adapt to adult life, and learn various important skills. However, there were several aspects that inhibit the achievement of the developmental tasks, for instance, off-task behavior, in which students disengaged from the learning environment by performing unrelated behavior. The occurrence of off-task behavior phenomena in primary school students needs to be addressed. Therefore, this research aims at investigating the profile of off-task behavior in primary school students. This quantitative research was conducted using the instruments of off-task behavior. This research involved 25 fifth grade primary school students in one private primary school in South Jakarta. The research results revealed that there were 60% of the students who were categorized performing moderate rate of off-task behavior with motoric aspect was the highest rare (38.7%).